Pemanfaatan Abu Kulit Kakao (Theobroma Cocoa L) Sebagai Sumber Kalium dan Taraf Kadar Air Tanah Berbeda pada Tanaman Jagung - Patty, Jacob Richard; Ririhena, Rhony Einstein; Leiwakabessy, Christoffol (JURNAL PERTANIAN KEPULAUAN, 2023)
Waste derived from plant material can be used as a source of plant nutrients. These waste products can be processed into compost to increase soil organic matter. The study aimed to determine the effect of cocoa peel ash application on drought conditions and natural sources of potassium for the growth and production of maize plants. The research design is a Factorial experiment in a Completely Randomized Design consisting of two treatments, namely: the amount of water application equivalent to rainfall (R): (R1) 70 mm / month, (R2) 80 mm / month, and (R3) 90 mm / month; fertilization of cocoa skin ash (K): control (K0), 100 kg/ha (K1), 150 kg/ha (K2), 200 kg/ha (K3), and, (K4) 250 kg/ha repeated 3 times. The results showed that the interaction between cocoa bark ash fertilization and the amount of water application equivalent to rainfall had a very noticeable effect on plant height and leaf area variables, while stem diameter changes had a noticeable effect. Fertilization treatment of 250 kg/ha (K4) best affects plant height, stem diameter, leaf area, and dry weight. The dose of cocoa husk ash fertilization of 200 kg/ha gives the best results on the weight of the seeds per plant, while the dose of 150 kg/ha is best at the weight of 100 seeds. Treatment of the amount of water application equivalent to rainfall of 90 mm/month gives the best results on leaf area, seed weight per plant, weight of 100 seeds, dry weight of plants, and harvest index